دور الأستاذ في تعديل وتوجيه سلوك التلاميذ أثناء حصة التربية البدنية في مرحلة التعليم المتوسط - دراسة ميدانية لمتوسطة: الشهيد لكحل أحمد/السعيد بونوغة - بن شويخ ، محمد; Supervisor : أوشن ، بوزيد (Mohamed Boudiaf University of M'Sila, 2025)
الملخص: عنوان الدراسة: دو دور الأستاذ في تعديل وتوجيه سلوك التلاميذ أثناء حصة التربية البدنية في مرحلة التعليم المتوسط - دراسة ميدانية لمتوسطة: الشهيد لكحل أحمد/السعيد بونوغة أهداف الدراسة: - التعرف على العلاقة بين ممارسة النشاط البدني الرياضي المدرسي وسلوك التلميذ من حيث النشاط الجسدي اليومي. - التعرف على دور النشاط البدني الرياضي التربوي في تنمية السلوك الصحي لدى التلاميذ. - التعرف على دور النشاط البدني الرياضي التربوي في تنمية السلوك الغذائي الصحي لدى التلاميذ - التعرف على دور النشاط البدني الرياضي التربوي في تنمية سلوك الامتثال للتعليمات الطبية لدى التلاميذ. - التعرف على دور النشاط البدني الرياضي التربوي في تنمية السلوك الصحي العام لدى التلاميذ. التساؤل العام الدراسة: ما هو دور الأستاذ في توجيه وتعديل سلوك التلاميذ أتناء حصة التربية البدنية والرياضية؟ التساؤلات الجزئية: 1-هل لشخصية الأستاذ دور في توجيه وتعديل سلوك التلاميذ أثناء حصة التربية البدنية والرياضية؟ 2-ما هو دور الأستاذ في تحقيق الانضباط للتلاميذ أثناء حصة التربية البدنية والرياضية؟ 3-ما هو دور الأستاذ في تحقيق التواصل لدى التلاميذ أثناء حصة التربية البدنية والرياضية؟ 4-هل للأستاذ دور في التقليل من العنف الجسدي واللفظي للتلاميذ أثناء حصة التربية البدنية والرياضية؟ الفرضية العامة للدراسة: للأستاذ دور في تعديل وتوجيه سلوك التلاميذ أثناء حصة التربية البدنية والرياضية. الفرضيات الجزئية _ لشخصية الأستاذ دور في تعديل وتوجيه سلوك التلاميذ أثناء حصة التربية البدنية والرياضية. _ للأستاذ دور إيجابي في تحقيق الانضباط لدى التلاميذ أثناء حصة التربية البدنية والرياضية. _ للأستاذ دور هام في تحقيق التواصل لدى التلاميذ أثناء حصة التربية البدنية والرياضية. _ للأستاذ دور في التقليل من العنف الجسدي واللفظي للتلاميذ أثناء حصة التربية البدنية والرياضية. المنهج المتبع في الدراسة: تم استخدام المنهج الوصفي الأدوات المستخدمة في الدراسة: تم استخدام استمارة الاستبيان كأداة لجمع البيانات الكلمات المفتاحية بالعربية: الأستاذ، التعديل والتوجيه، السلوك، التلاميذ، حصة التربية البدنية، مرحلة التعليم المتوسط بالإنجليزية: he teacher, modification and guidance, behavior, students, physical education class, intermediate education stage جاء هذا البحث في 06 فصول: الجانب التمهيدي: وفيه تناولت الإشكالية والتساؤلات والفرضيات وأهداف البحث وأهمية البحث والتعليق عن أسبابه وكذا شرح المصطلحات والمفاهيم المتعلقة بالبحث والدراسات السابقة والمشابهة ونقدها. الفصل الأول يتعلق بشخصية أستاذ التربية البدنية والرياضية ويحتوي مفهوم الشخصية، خصائص الشخصية، شخصية المربي، الصفات المثالية لأستاذ التربية البدنية والرياضية، خصائص الأستاذ كشخصية مدرسية قيادية، العلاقة بين الأستاذ والتلميذ في التربية البدنية والرياضية، الفصل الثاني: تناولنا فيه مفهوم تعديل وتوجيه سلوك التلاميذ في حصة التربية البدنية والرياضية وكل فصل يبدأ بمقدمة وينتهي بخلاصة. الفصل الثالث: تعرضنا فيه إلى الطرق المنهجية للبحث، فحددنا المنهج المتبع، والمتغيرات الخاصة بالبحث، والدراسة الاستطلاعية، ومجتمع البحث، وعينته، وأدوات البحث لجمع البيانات، وصدق وثبات الأداة، ومجالات البحث والوسائل الإحصائية لمعالجة البيانات الفصل الرابع: خصص لعرض وتحليل نتائج الاستبيان. الفصل الخامس: خصص لمناقشة النتائج على ضوء الفرضيات والدراسات السابقة، وأخيرا أنهينا بحثنا هذا باستنتاج عام الفصل السادس: قمنا بمجموعة من الاقتراحات والتوصيات وأنهينا دراستنا بخاتمة. من أهم النتائج التي توصل إليها الباحث: - للأستاذ دور في تعديل وتوجيه سلوك التلاميذ أثناء حصة التربية البدنية والرياضية. _ لشخصية الأستاذ دور في تعديل وتوجيه سلوك التلاميذ أثناء حصة التربية البدنية والرياضية. _ للأستاذ دور إيجابي في تحقيق الانضباط لدى التلاميذ أثناء حصة التربية البدنية والرياضية. _ للأستاذ دور هام في تحقيق التواصل لدى التلاميذ أثناء حصة التربية البدنية والرياضية. _ للأستاذ دور في التقليل من العنف الجسدي واللفظي للتلاميذ أثناء حصة التربية البدنية والرياضية. أهم التوصيات: _ ضرورة تنمية العلاقة بين الأستاذ والتلميذ من اجل الوصول إلى الأهداف والأبعاد المنشودة التي تهدف إليها حصة التربية البدنية والرياضة في الوسط المدرسي. _ ضرورة تبصير الأستاذ بأدواره ومهامه المهنية والاجتماعية والتربوية والأخلاقية وذلك بالاهتمام بتحسين برامج إعداد وتدريس وتكوين الأستاذ في ضوء مستحدثات العصر والتقنيات الحديثة. _ إقامة دورات تكوينية لأساتذة التربية البدنية والرياضية والرفع من كفاءته. _ الانتقاء الجيد للأساتذة الأكفاء والجيدين ذوي القدرات والمهارات العالية والذي من شأنه تكوين الأجيال. _ اخذ المسؤولين والمفتشين والقائمين على التعليم بصفة عامة والتربية البدنية بصفة خاصة النتائج التي توصل إليها هذا البحث بعين الاعتبار.   Summary: Study title: The role of the professor in modifying and directing the behavior of students during the physical education class in the intermediate education stage - an intermediate field study: Martyr Lakhal Ahmed/Al-Saeed Bonouga Study objectives: -To identify the relationship between the practice of school sports physical activity and the behaviour of the pupil in terms of daily physical activity. -To identify the role of physical activity sports educational in the development of healthy behavior in pupils. -To identify the role of physical activity sports educational in the development of healthy eating behavior in pupils -To identify the role of physical activity sports-pedagogical in the development of behavior of compliance with medical instructions in pupils. -To identify the role of physical activity sports educational in the development of general health behavior in pupils. The general question of the study: What is the role of the professor in directing and modifying the behavior of students during the physical education and sports class? Partial questions: 1-Does the professor’s personality play a role in directing and modifying students’ behavior during physical education and sports class? 2-What is the role of the professor in achieving discipline for students during physical education and sports class? 3-What is the role of the professor in achieving communication among students during physical education and sports class? 4-Does the teacher have a role in reducing physical and verbal violence against students during physical education and sports class? General hypothesis of the study: The professor has a role in modifying and guiding the behavior of the pupils during the physical education and sports class. Partial hypotheses _ The professor’s personality has a role in modifying and directing the behavior of students during the physical education and sports class. _ The professor has a positive role in achieving discipline among students during physical education and sports class. _ The professor has an important role in achieving communication among students during the physical education and sports class. _ The professor has a role in reducing physical and verbal violence against students during physical education and sports class. Method followed in the study: a descriptive approach was used Instruments used in the study: The questionnaire form was used as a data collection instrument Keywords: physical activity, sports, education, healthy behavior, middle school This research came in 6 chapters: The introductory aspect: It dealt with the problem, questions, hypotheses, research objectives, the importance of research, commenting on its causes, as well as explaining and criticizing terms and concepts related to previous and similar research and studies. The first chapter relates to the personality of the physical and sports education professor and contains the concept of personality, personality characteristics, the personality of the educator, the ideal qualities of the physical and sports education professor, the characteristics of the professor as a leadership school personality, the relationship between the professor and the student in physical and sports education, Chapter Two: In it, we discussed the concept of modifying and directing the behavior of students in the physical education and sports class.Each chapter begins with an introduction and ends with a summary. Chapter Three: In it, we presented the methodological methods of the research.We identified the method used, the variables specific to the research, the exploratory study, the research community and its sample, the research tools for collecting data, the validity and reliability of the tool, the areas of research and the statistical means for processing the data Chapter 4: is devoted to the presentation and analysis of the results of the questionnaire. Chapter Five: is devoted to discussing the results in light of previous hypotheses and studies.Finally, we ended our research with a general conclusion Chapter 6: We made a set of suggestions and recommendations and ended our study with a conclusion. This research came in 6 chapters: Chapter One: The methodological framework of the study, in which we discussed the study’s problem and questions, in addition to the study’s hypotheses, the reasons for choosing the topic, the importance and objectives of the study, and then we presented some previous and similar studies and commented on them. The second chapter: We discussed educational sports physical activity, in which we touched on the concept of educational sports physical activity, its objectives and importance, in addition to its characteristics and motivations.We also touched on the functions of educational sports activity, its classifications and foundations. Chapter Three: We touched on health behavior, through which we touched on the definition of health behavior, its patterns and dimensions, in addition to the most important theories explaining health behavior.We also touched on the factors of acquiring health behavior and the factors affecting it. As for the applied aspect, we divided it into two chapters: Chapter Four: The methodological framework of the study, in which we discussed the exploratory study, the areas of study, the method followed in the study, the population and sample of the study, the study tools, and finally the statistical tools used in the study. Chapter 5: Presentation and interpretation of study results. Chapter 6: Conclusions and Suggestions Among the most important findings reached by the researcher: The professor has a role in modifying and guiding the behaviour of pupils during the physical education and sports class. _ The professor’s personality has a role in modifying and directing the behavior of students during the physical education and sports class. _ The professor has a positive role in achieving discipline among students during physical education and sports class. _ The professor has an important role in achieving communication among students during the physical education and sports class. _ The professor has a role in reducing physical and verbal violence against students during physical education and sports class. The most important recommendations: _ The necessity of developing the relationship between the teacher and the student in order to reach the desired goals and dimensions aimed at by the physical education and sports class in the school environment. _ The need for the professor to be informed of his professional, social, educational and moral roles and tasks by paying attention to improving the professor’s preparation, teaching and training programs in light of the latest developments of the times and modern technologies. _ Holding training courses for teachers of physical education and sports and raising their efficiency. _ Good selection of competent and good professors with high abilities and skills who will form generations. _ Officials, inspectors, and those in charge of education in general and physical education in particular took the findings of this research into consideration.
Keywords: التعديل والتوجيه; ، السلوك، التلاميذ; حصة التربية البدنية; مرحلة التعليم المتوسط